The effect of turbine characteristics on the thermodynamics and compression process of a simple OWC device. (May 2022) - Molina, A.; Jiménez-Portaz, M.; Clavero, M.; Moñino, A.
Abstract: The Oscillating Water Column (OWC) is leading the Wave Energy Converters in terms of efforts and research devoted. However, the efficiency achieved by these devices is still low enough to become a real renewable energy source. The main objective of this paper is to study the influence of the turbine characteristics in the thermodynamic process inside the OWC chamber, which is defined by the polytropic exponent associated with the polytropic process. Wind tunnel tests have been carried out to obtain experimental data under stationary flow, applying a real gas model where moisture plays a fundamental role. The results show the importance of the turbine characteristics and its effects on the thermodynamic compression process, affecting the power output of the OWC device. In conclusion, this study provides a better understanding of the OWC performance to improve its efficiency.